The Existence and Multiplicity of Positive Solutions for Second-Order Periodic Boundary Value Problem - Feng Wang; Fang Zhang; Fuli Wang (Journal of Function Spaces and Applications)
The existence and multiplicity of positive solutions are established for second-order periodic boundary value problem. Our results are based on the theory of a fixed point index for A-proper semilinear operators defined on cones due to Cremins. Our approach is different in essence from other papers and the main results of this paper are also new.